2017
DOI: 10.4103/0019-557x.200254
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with survival and lost to follow-up of cervical cancer patients in a tertiary cancer centre in rural Kerala

Abstract: Cancer cervix is the second common cause of cancer death in India. It is the most curable form of any human cancer if detected at the precancerous stage. Although several factors determine the survival of the disease, the clinical stage at presentation is the single most important predictor of long-term survival. The present study aimed to describe the performance and follow-up status and 5-year survival experience of the cervical cancer patients registered between 2010 and 2011 by the hospital registry of Mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…A survey conducted in central state of India, Madhya Pradesh, reported availability of laboratory services, human resources, drugs, equipments and point-of-care supply domains to be 37.1, 49.0, 56.1, 67.9 and 80.9%, respectively, at community health centers (CHCs) and 11.8, 18.2, 44.2, 55.1, and 55.3%, respectively, at primary health centers (PHCs) [3]. Another report from a southern state (Kerala) reported that among the 227 cervical cancer patients 216 (95.2%) of the patients completed the initially planned treatment and among them only 30.4% had regular follow-up, while the rest 69.6% were lost to follow-up [4]. This is the usual scenario across India, where patients visit a tertiary care center in the advanced stage of the disease, take initial treatment and then are unable to come for follow-up.…”
Section: Introductionmentioning
confidence: 99%
“…A survey conducted in central state of India, Madhya Pradesh, reported availability of laboratory services, human resources, drugs, equipments and point-of-care supply domains to be 37.1, 49.0, 56.1, 67.9 and 80.9%, respectively, at community health centers (CHCs) and 11.8, 18.2, 44.2, 55.1, and 55.3%, respectively, at primary health centers (PHCs) [3]. Another report from a southern state (Kerala) reported that among the 227 cervical cancer patients 216 (95.2%) of the patients completed the initially planned treatment and among them only 30.4% had regular follow-up, while the rest 69.6% were lost to follow-up [4]. This is the usual scenario across India, where patients visit a tertiary care center in the advanced stage of the disease, take initial treatment and then are unable to come for follow-up.…”
Section: Introductionmentioning
confidence: 99%
“… 8 26 27 On the other hand, comparatively higher proportion of patients presented with stage I disease in rural Kerala (12.80%) and Trivandrum (11.10%), where state is running national CC screening program. 28 29 These studies stressed on the importance of formulating public health policies with improving awareness and implementation of CC screening programs. Nepal developed screening services in limited areas.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have investigated the association between late stage disease at presentation and low survival rather than LTFU [11,12,18,19]. A few studies that have assessed stage at presentation and LTFU in South India showed similar associations between advanced stage at presentation and being LTFU [8,10]. Patients arriving into care at a later stage of illness may seek care elsewhere or outside the system if cure within the formal system is deemed unlikely.…”
Section: Discussionmentioning
confidence: 99%